The Effect of Emotional Labor of College Administrative Service Workers on Job Attitudes: Mediating Effect of Emotional Labor on Trust and Organizational Commitment - Han, Sang-Lin; Shim, Hyeon-Sook; Choi, Won Jun (Frontiers in Psychology, 2018)
Service providers working for a service organization are asked to express such positive emotions as joy, pleasure, and politeness required at the organizational level rather than their natural emotions they are experiencing at the moment. They cannot express their emotion they are actually going through and accordingly, their level of emotional labor and emotional dissonance influence on their job commitment and trust toward their organization. This study thus set out to investigate the effects of leading variables of emotional labor on the level of emotional labor and the impact of emotional labor on organizational trust and organizational commitment with a subject group of college administrative staffs. Three underlying factors such as job stress, intimacy, and professionalism were identified as the determinants of emotional labor. Conceptual background about job stress, intimacy, emotional labor, and organizational effectiveness as the core variables of the study was investigated. Based on the conceptual background and our research questions, 5 research hypotheses and the proposed research model regarding the effects of emotional labor on organizational commitment and trust were developed. We also tried to include the moderating effects of work environment and gender of service providers on the research model. Unlike many different studies on emotional labor from the traditional perspective of service, this study also offers a practical implication by expanding and applying it to the field of college administrative service, which is an area where service providers are in the different working environment from the traditional company work environment. Finally, the managerial implications and the limitations of the study were also discussed.